A Novel Lineage of Ceftriaxone-resistant Salmonella Typhi From India That Is Closely Related to XDR S. Typhi Found in Pakistan. (20th December 2019) - Sah, Ranjit; Donovan, Suzanne; Seth-Smith, Helena M B; Bloemberg, Guido; Wüthrich, Daniel; Stephan, Roger; Kataria, Sushila; Kumar, Mahadevan; Singla, Sonam; Deswal, Vikas; Kaur, Amarjeet; Neumayr, Andreas; et al.
Abstract: Two MDR Salmonella Typhi isolates from India were found by whole genome sequencing to be closely related to the 2016 XDR S. Typhi outbreak strain from Pakistan. The Indian isolates have no chromosomal antimicrobial resistance cassette but carry the IncY plasmid p60006. Both isolates are susceptible to chloramphenicol, azithromycin, and carbapenems.